ANALISIS KEBUTUHAN TENAGA ADMINISTRASI SEKOLAH PADA JENJANG SMA DAN SMK - Bayu Pramudya; Ibrahim Bafadal; Teguh Triwiyanto (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
Abstrack: This study aims to, (1) find out the number of shool administration staff at Senior and Vocational High School in District of Ngawi; (2) Knowing how high the school administration staff needs are based on the ratio of students for the next ten years; (3) Knowing how high the percentage of the needs of school administration staff at Senior and Vocational High School in District of Ngawi. This study uses a quantitative approach with a descriptive projective research design. Instrument in this study uses documentation method by recruiting data in the field. The data analysis technique used is a comparison of the ratio of school administration staff to the ratio of student, method of trend of parabolic, attrition, and moderate needs. The results of this study indicate: (1) The existence the count of administration staff at senior and vocational high school in Ngawi Regency in 2018-2027 (2) Needs for senior and vocational high school administration staff in Ngawi Regency is based on the ratio of students (3) Percentage of need for administration staff of senior and vocational high school at Ngawi District in 2018-2027. Keywords: needs analyst, school administration staff Abstrak: Penelitian ini bertujuan untuk, (1) Mengetahui Jumlah Tenaga Administrasi Sekolah  Sekolah Menengah Atas (SMA) dan Sekolah Menengah Kejuruan (SMK) Negeri di Kabupaten Ngawi; (2) Mengetahui seberapa tinggi kebutuhan TAS berdasarkan rasio peserta didik selama sepuluh tahun yang akan datang; (3) Mengetahui seberapa tinggi tingkat persentase kebutuhan tenaga administrasi sekolah SMA dan SMK Negeri di Kabupaten Ngawi. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan penelitian deskriptif proyektif. Instrumen dalam penelitian ini menggunakan metode dokumentasi dengan menyalin data yang ada di lapangan. Teknik analisis data yang digunakan adalah perbandingan rasio tenaga adinistrasi sekolah dengan rasio peserta didik, metode trend parabola, atrisi, dan kebutuhan moderat. Hasil penelitian ini menunjukan (1) Keberadaan jumlah tenaga administrasi sekolah SMA dan SMK Negeri di Kabupaten Ngawi pada Tahun 2018-2027; (2) Kebutuhan tenaga administrasi sekolah SMA dan SMK Negeri di Kabupaten Ngawi berdasarkan rasio peserta didik; (3) Persentase kebutuhan tenaga administrasi sekolah SMA dan SMK Negeri di Kabupaten Ngawi Tahun 2018-2027. Kata Kunci: analisis kebutuhan, tenaga administrasi sekolah